KONSEP PENGUASAAN HAK CIPTA ATAS FOLKLOR OLEH NEGARA DALAM KERANGKA PERLINDUNGAN HUKUM HAK CIPTA DI INDONESIA - , Arif Lutviansori, SH, Haryanto, S.H., MKn. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of the study was conducted to determine the form of implementation of copyright regulation of the folklore by the State within the framework of the copyright regime, so as to know the weaknesses and strengths of the existing concept of mastery. Second, knowing the position of the State and analyzing as the copyright holder of folklore in relation to the concept of copyright protection in Indonesia. Third, knowing the form of benefit sharing between State as a copyright holder of folklore in indigenous communities as parties who conserve the folklore to ensure the rights of indigenous folklore raiser. This study is a descriptive type of qualitative research, using the method of approach to the legislation (Statute approach) and the philosophical analysis of the data with content analysis (content analysis). Data collection techniques using literature study (library research) and interview, while the data sources used were primary and secondary data sources consisting of primary legal materials, secondary legal materials, and tertiary. Based on the analysis has been performed, the conclusions in this study are: First, the implementation arrangements folklore by copyright in the country there are still some obstacles in the juridical perspective. Among the constraints that now is the absence of experienced technical rules governing the protection and control of folklore by the State, both Government Regulation (Peraturan Pemerintah) and UUHC promised by the bill will be issued and PTEBT which until now has not finished its discussion. Second, the position of the State in the mastery of folklore are the copyright holder is far more focused on recording capacity, inventories, and folklore. In the context of a dispute occurs, or misuse of this folklore countries contribute more towards the completion of the process of cultural diplomacy, not to the extent legally completion. Position as a Sovereign State Copyright folklore is also not sufficient in providing legal action against the misuse of folklore by the parties in the country, due to the absence of legal foundation to strengthen the position of the State in the handling of abuse folklore. Third, Up to now there is no clear mechanism of benefit sharing between countries with indigenous peoples. This is again due to the absence of comprehensive rules on the protection of folklore in the perspective of copyright, which is then coupled with the absence of technical rules that explain the issue.